Putusan dan Penetapan PA Kuningan Nomor 492/Pdt.G/2022/PA.Kng tentang Gugurnya Ikrar Talak Suami dalam Cerai Talak: Perspektif Hukum Islam dan Hukum Positif - Bakri, Mukhlis (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2024)
The case of the cancellation of a husband's divorce vow in a divorce talak is not a new thing, in fact this case has often happened in almost all regions in Indonesia. This happened because on the day of the hearing for the divorce pledge the applicant was not present, so that the applicant's or husband's application for the divorce pledge was invalid and did not have permanent legal force. The purpose of this research is to find out whether the judge's considerations used in deciding case Number 492/Pdt.G/2022/PA.Kng are in accordance with Islamic law and positive law or not, then analyzed using a comparative study. The research method used by the author is qualitative research by combining two types of data, namely data obtained from field research in the form of structured interviews and documentation at the Kuningan Religious Court, combined with library research data in the form of documents of decisions and determinations of judges regarding the divorce talak case. The data that the author obtained was then reduced, presented and concluded using descriptive-comparative analysis techniques. Based on the research carried out, conclusions were obtained including: 1) The basis that is the legal source used by the Judge in the process of deciding on divorce talak at the Kuningan Religious Court, namely using the Law, Het Herziene Indonesisch Reglement (HIR), and Reglement voor de Buitengewesten (RBg), as well as non-juridical considerations (Islamic Law) Judges use the Compilation of Islamic Law and Judges also include verses from the Koran. 2) The judge's consideration regarding the husband's right to give talak was in accordance with Islamic law and positive law. 3) In the comparative analysis aspect regarding the divorce vow before a judge is in accordance with positive law, but not in accordance with Islamic law. 4) The cancellation of the husband's talak status in case Number 492/Pdt.G/2022/PA.Kng was due to the husband's absence on the day of the trial for witnessing the talak vow which was in accordance with positive law but not in accordance with Islamic law, due to the consequences experienced by the husband who imposing divorce on the wife in the form of the husband's obligation to provide support for his wife and children, so that in this case it has harmed both parties for the future. Keywords: Divorce, Divorce Talak Vow, Cancellation of Husband's of Divorce Talak.